Internal Branding dalam Meningkatkan Kinerja Pegawai dengan Moderasi Beragama (MB) sebagai Variabel Moderator di Lingkungan Kantor Wilayah Kementerian Agama Provinsi Jambi - Ovi Oktavina; Sry Rosita; Ade Perdana Siregar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of internal branding on employee performance and examine the role of religious moderation as a moderating variable in this relationship in public sector organizations. The study used a quantitative approach with a survey method, where data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that internal branding had a positive and significant effect on employee performance, indicating that understanding and internalizing organizational values ​​can improve employee work behavior and performance quality. Religious moderation was also shown to have a positive and significant effect on employee performance, indicating that religious moderation values ​​play a role in shaping professional, inclusive, and service-oriented work attitudes. However, religious moderation was not shown to moderate the relationship between internal branding and employee performance (p-value = 0.781 > 0.05), so the effect of internal branding on employee performance is relatively consistent at various levels of religious moderation. This study concludes that internal branding and religious moderation are two factors that directly contribute to improving employee performance and provide implications for public sector organizations in strengthening human resource management strategies based on organizational values ​​and moderate religious values.